Linewidth dependence of NbN-based microwave kinetic inductance detectors. (September 2019) - Negishi, S; Mikami, H; Hashimoto, S; Nakajima, K; Terai, H; Tanaka, S; Ariyoshi, S
Abstract: We analysed, fabricated, and characterised niobium nitride (NbN)-based microwave kinetic inductance detectors (MKIDs) with a rewound strip structure (spiral-MKIDs). To control resonance characteristics precisely, the linewidth ( w ) dependence of rewound spiral resonators varying between w = 10, 20, and 40 μm was analysed using an electromagnetic field simulator; the resonance frequencies ( f 0 's) were obtained as 4.42, 4.58, and 5.15 GHz respectively, proving that the inductance decreases as the w increases. To verify the simulation results experimentally, NbN-based MKID arrays with different linewidths were fabricated on 10×10 mm 2 sapphire substrates, and cooled down to 3 K. The microwave characteristics with a vector network analyser, and f 0 's were found to be 4.11, 4.23, and 4.85 GHz for the MKIDs with w = 10, 20, and 40 μm, respectively. These values are in agreement with the simulation results within 7.6% accuracy. The other resonance characteristics such as the scattering-matrix element ( S 21 ) and loaded quality factor ( Q L ) showed the similar w dependence with the simulation. Spiral-MKIDs with narrower w is expected to have better detector performance owing to shallower S 21 and higher Q L .